Asta's Framework Conferralism Analysis of Women's Bodies in The Hidden Face of Eve by Nawal el Saadawi - Nurfitriani, Putri; Hannah, Neng (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
This article aimed to discuss the concept of women's bodies that Nawal el Saadawi wrote and portrayed in her book The Hidden Face of Eve, by using the conferralism framework introduced by Asta, an Icelandic contemporary philosopher. A literature review method with a feminist approach was used in this research to reveal phenomena that happened in women’s life and also to conduct non-exploitative research. The findings in this research are, Asta offers a conferralism framework to stress that social properties that are enforced on a person, likely have another person’s power in it. Conferralism gave a firm new insight into the enforcement of social categories to an individual, it helps to uncover women’s experiences from Nawal el Saadawi’s writing. Where women’s bodies are strictly attached to some properties and restricted to only exist in some areas.